1985
DOI: 10.1097/01241398-198509000-00146
|View full text |Cite
|
Sign up to set email alerts
|

The Athletic Health Care and Training Program (A Comprehensive Approach to the Prevention and Management of Athletic Injuries in High Schools)

Abstract: The Athletic Health Care and Training Program was developed to meet the educational, organizational and record-keeping needs of the interscholastic athletic program of the Seattle Public Schools. The program components were the education of coaches, school nurses and student trainers; development of a centralized training room; implementation of written procedures, and establishment of a record-keeping system. At the end of the three-year study period, schools involved in the program were better prepared to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…However, they concluded that lower extremity alignment was not a risk factor for running injury in their study. 35 Similarly, Hreljac et al 14 measured arch height of 40 club runners using calipers in a standing position, but found that this measure did not discriminate between injured and noninjured runners. They concluded that preseason screens would not successfully predict running injuries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, they concluded that lower extremity alignment was not a risk factor for running injury in their study. 35 Similarly, Hreljac et al 14 measured arch height of 40 club runners using calipers in a standing position, but found that this measure did not discriminate between injured and noninjured runners. They concluded that preseason screens would not successfully predict running injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Wen et al 35 as- sessed the arch index (navicular height divided by truncated foot length) of over 300 runners compared with previous injury questionnaires and reported a low right arch index was related to previous shin injury within the past year. However, they concluded that lower extremity alignment was not a risk factor for running injury in their study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations